Pain management in Guillain-Barre syndrome: A systematic review (2015)
Objetivo: Material y métodos: Resultados: Conclusiones: Introduction: Pain is a common symptom in patients with Guillain-Barre syndrome. Intensity is moderate to severe in most cases and pain may persist after resolution of the disease. Objective: Identify the most appropriate analgesic therapy for pain management in patients with Guillain-Barre syndrome. Material and methods: Systematic review and selection of scientific articles on treatment of pain in Guillain-Barre syndrome patients, published between January 1985 and December 2012. We included only randomised, double-blind, controlled trials assessing the effectiveness of drugs for pain management in these patients. Results: Four articles met the inclusion criteria. One evaluated the use of gabapentin, another evaluated carbamazepine, a third compared gabapentin to carbamazepine, and the last evaluated use of methylprednisolone. Both carbamazepine and gabapentin were useful for pain management. Patients experienced lower-intensity pain with gabapentin treatment in the study comparing that drug to carbamazepine. Methylprednisolone was not shown to be effective for reducing pain. The published data did not permit completion of a meta-analysis. Conclusions: There is no robust evidence at present that would point to a single treatment option for this disorder. Further clinical studies of larger patient samples and with a longer duration are needed to characterise types of pain for each patient and measure pain intensity in an objective way. © 2013 Sociedad Española de Neurología.